KONSEP PENDIDIKAN MULTIKULTURAL DAN IMPLEMENTASINYA DALAM PEMBELAJARAN - Sani, Mufid Rizal (Jurnal Tawadhu, 2017)
Multicultural education is an education that offers an alternative through the implementation of educational strategies and concepts based on the diversity utilization in society, especially those that are present in learners such as ethnic plurality, culture, language, religion, social status, gender, ability, age and race. This educational strategy is not only aimed to make students easily understand the lessons they learn, but also to raise their awareness to always behave humanist, pluralist, and democratic. The most important thing that needs to be underlined in the implementation of multicultural education is that a teacher is not only required to master and be professionally taught, but a teacher must also be able to inculcate the core values of multicultural education such as democracy, humanism, and pluralism.Multicultural education must be internalized in a learning process that transforms an essential, prejudiced and discriminatory monocultural perspective into a multiculturalist perspective that values diversity and difference, tolerance and open attitude (inclusive). Such a paradigm shift demands a transformation to education that is not limited to mere cognitive dimensions. Moreover, it also demands changes in the affective and psychomotor dimensions.